2016
DOI: 10.1016/j.oregeorev.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

S, Pb, and Sr isotope geochemistry and genesis of Pb–Zn mineralization in the Huangshaping polymetallic ore deposit of southern Hunan Province, China

Abstract: The Huangshaping Pb-Zn-W-Mo polymetallic deposit, located in southern Hunan 9 Province, China, is one of the largest deposits in the region and is unique for its metals 10 combination of Pb-Zn-W-Mo and the occurrence of significant reserves of all these metals. The 11 deposit contains disseminated scheelite and molybdenite within a skarn zone located between 12 Jurassic granitoids and Carboniferous sedimentary carbonate, and sulfide ores located within distal 13 carbonate-hosted stratiform orebodies. The metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…The higher ΣREE in granite porphyry skarn mineralization could be explained by the influence of high‐temperature, high‐salinity magmatic‐metasomatized fluids, determined by Banks, Yardley, Campbell, and Jarvis () to be the best candidates for carrying large amounts of REE. Previous fluid inclusion microthermometry analyses revealed that Stage II mineralization took place in a significantly higher temperature and more saline environment, compared to other mineralization stages (Figure ; Ding, Ma, Lu, Zhang, & Zhang, , Ding et al, , ; Huang et al, ; Li et al, ). Moreover, δ 18 O values also differ between W–Mo ores ( δ 18 O = 8.10–8.41‰) and Cu ores ( δ 18 O = 4.34–4.96‰; Li et al, ), suggesting that two kinds of redox environments were favoured for the different types of ores.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The higher ΣREE in granite porphyry skarn mineralization could be explained by the influence of high‐temperature, high‐salinity magmatic‐metasomatized fluids, determined by Banks, Yardley, Campbell, and Jarvis () to be the best candidates for carrying large amounts of REE. Previous fluid inclusion microthermometry analyses revealed that Stage II mineralization took place in a significantly higher temperature and more saline environment, compared to other mineralization stages (Figure ; Ding, Ma, Lu, Zhang, & Zhang, , Ding et al, , ; Huang et al, ; Li et al, ). Moreover, δ 18 O values also differ between W–Mo ores ( δ 18 O = 8.10–8.41‰) and Cu ores ( δ 18 O = 4.34–4.96‰; Li et al, ), suggesting that two kinds of redox environments were favoured for the different types of ores.…”
Section: Discussionmentioning
confidence: 95%
“…This conclusion is supported by the relatively large variation in 87 Sr/ 86 Sr ratios (Figure b) and the positive correlation between 87 Sr/ 86 Sr ratios and δ 18 O values (Li et al, ). On the other hand, the wall rock (carbonate) in the Huangshaping deposit does have extremely high Sr contents (initial 87 Sr/ 86 Sr = 0.707484–0.708034; Ding, Ma, Lu, Zhang, & Zhang, ), and contamination by carbonates may have significantly changed the Sr isotope signatures in mineralized granitoids. All of this evidence may indicate that the granite porphyry experienced pronounced fluid–rock interaction and was metasomatized by derived fluids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcropping strata in the belt consists of Sinian to Cambrian low-grade metamorphic rocks, Devonian to Lower Triassic limestone intercalated with clastic rocks, and Upper Triassic to Tertiary sandstone and siltstone. The Yangshanian granites intrude extensively in southern Hunan with the largest being the Qitianling intrusion [31][32][33], and they control the formation of a number of large-scale porphyry, skarn, and vein-type W-Sn-Pb-Zn deposits (Figure 1b), e.g., the Shizhuyuan [34], Baoshan [35], Huangshaping [36][37][38], Xianghualing [39], Xintianling [35], Yaoganxiang [30], Baiyunxian, and Furong deposits [35,40].…”
Section: Geologic Settingmentioning
confidence: 99%